KARAKTERISTIK AKAR BEREKTOMIKORIZA PADA Shorea pinanga, Pinus merkusii DAN Gnetum gnemon - Melya Riniarti; Irdika Mansur; Arum Sekar Wulandari; Cecep Kusmana (PERENNIAL, 2010)
Morphology and anatomy characteristics often used to identify ectomycorrhizal fungi. We used three Scleroderma spp. (Scleroderma columnare, S. dictyosporum), and S. sinnamariense) and inoculated to Shorea pinanga, Pinus merkusii, and Gnetum gnemon. After 6,8, and 10 months, each root tips were collected to determined hyphae colour, branching pattern, clamp-connection, hartig net and mantle. This result revealed that S. sinnamariense did not form association with S. pinanga and P. merkusii but form association with G. gnemon. On the other hand, S. columnare and S. dictyosporum could form association with all the host plants. S. columnare and S. dictyosporum formed white hyphae while S. sinnamariense formed yellow hyphae with monopodial branching pattern. The depth of hartig net and mantle was increased by timed. Key words: ectomycorrhizal fungi, hartig net, mantle, Scleroderma